A cost and economic evaluation of the Leeds personality disorder managed clinical network—A service and commissioning development initiative. (17th February 2016) - Kane, Eddie; Reeder, Neil; Keane, Kimberley; Prince, Sharon
ABSTRACT: In the UK, patients with personality disorders presenting complex needs frequently experience an unhelpful pattern of acute treatment followed by community care—with associated high cost implications for services. With UK mental health resources under severe pressure, this leaves commissioners with difficult decisions to make. Yet studies on cost‐effectiveness in respect of personality disorder treatment are scarce, particularly for treatments taking place outside of major teaching hospitals in the USA. This paper studies the benefits of an intensive, holistic approach and finds that the Network achieved substantial reductions in health care usage and expenditure in the short to medium term. Copyright © 2016 John Wiley & Sons, Ltd.